Peculiarities of application of pulmonary rehabilitation program in patients with chronic obstructive pulmonary disease - Yu. G. Krylova; V. I. Trofimov; A. A. Potapchuk (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Comprehensive pulmonary rehabilitation is gradually becoming the «gold standard» in the treatment of chronic obstructive pulmonary disease. It includes physical training, correction of nutritional status, patient education, psychological and social support.